2007
DOI: 10.1021/jp0770615
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Length of Gold Nanowires with Large-Scale:  X-ray Absorption Spectroscopy Approaches to the Growth Process

Abstract: By utilizing the X-ray absorption approach, the gold ions evolving from the Au-Cl complex to Au rods have been elucidated. The theoretical simulation of X-ray absorption spectra further revealed the evolution of gold and concluded that ultrafine small clusters of gold (Au 13 ) formed after a reducing agent was added to the growth solution. A redesigned seed-assisted growth method, a serial addition of growth solution, was employed to achieve the goal of the consecutive support of gold. The development approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 83 publications
5
47
0
Order By: Relevance
“…Extended X-ray absorption fi ne structure (EXAFS) is a shortrange probe of structure and yielded results concerning local correlations around the absorbing atom, specifi cally the nearest neighbor interatomic distances and coordination numbers. [27][28][29] EXAFS was conducted to obtain better evidence of the structural parameters of ZnO-ZnS solid solution nanowire arrays. Figure 4 shows the Zn K-edge of ZnO and ZnO-ZnS [ 30 ] To compare with pristine ZnO nanowire, the electronic transition to p state along the c axis increased with the formation of ZnO-ZnS solid solution, indicating that orbital coupling occurred in c axis direction of ZnO nanowire.…”
mentioning
confidence: 99%
“…Extended X-ray absorption fi ne structure (EXAFS) is a shortrange probe of structure and yielded results concerning local correlations around the absorbing atom, specifi cally the nearest neighbor interatomic distances and coordination numbers. [27][28][29] EXAFS was conducted to obtain better evidence of the structural parameters of ZnO-ZnS solid solution nanowire arrays. Figure 4 shows the Zn K-edge of ZnO and ZnO-ZnS [ 30 ] To compare with pristine ZnO nanowire, the electronic transition to p state along the c axis increased with the formation of ZnO-ZnS solid solution, indicating that orbital coupling occurred in c axis direction of ZnO nanowire.…”
mentioning
confidence: 99%
“…The Ru-Ru distance in the Ru nanocluster catalysts was measured to be 2.6Å. In another study, growth of gold nanoparticles was monitored with XAS by Chen et al [127]. They found that small gold nanoclusters such as Au 13 were formed immediately after the introduction of the reducing agent into the gold acidic solution.…”
Section: Nanomaterials Made Ex Situmentioning
confidence: 99%
“…For selective adhesion of surfactant, after seed formation, organic molecules, strongly bind to specific crystal plane (e.g., high surface energy), provide kinetic control to extend along one-direction upon growing of the nanostructures [23]. Liu et al reported that addition of serial growth aqueous solution with gold precursor (HAuCl 4 ) into the gold seed solution at 30 s intervals created Au nanorods [23].…”
Section: Rod-like Particlesmentioning
confidence: 99%
“…Liu et al reported that addition of serial growth aqueous solution with gold precursor (HAuCl 4 ) into the gold seed solution at 30 s intervals created Au nanorods [23]. The evolution of the Au nanorods by a serial addition of growth solution was investigated through X-ray absorption spectra.…”
Section: Rod-like Particlesmentioning
confidence: 99%